The Moderating Effects of Risk and Subjective Norm Perception Towards Consumers’ Trust and Online Purchase Intention (International Journal of Psychosocial Rehabilitation, 2020)
This study was intended to examine the moderating effects of risk and subjective norm perception towards consumers’ trust and consumers’ online purchase intention on the purchasing of online products that belong to body care category. The samples in this study were 120 students of Universitas Esa Unggul who had made online purchase of the products that belong to body care category. The method used in this study was the non-hierarchical Anova or Cell Means method on which the values of the samples were calculated by using computer software. The results of this study showed that consumers' trust affected online purchase intention of the products within body care category with a significance value of 0.000. This study also found that moderating effect of risk towards consumers’ trust and online purchase intention had a significance value of 0.032.